PELATIHAN DAN PERANCANGAN ALAT PENDETEKSI KELAYAKAN AIR MINUM MENGUNAKAN MIKROKONTROLLER AT89S51 PADA SMK NEGERI 8 BATAM - agus; Johan, Dasman; Vivi Putri, Meylia; Lia Febrianti, Eka (Jurnal Pengabdian Masyarakat Bangsa, 2023)
Increasing the usability of computers can not only be used to process data but can also be applied in controlling various tools, one of which is detecting the feasibility of drinking water using the AT89S51 microcontroller. In this case the microcontroller is used to control the PH meter and LCD sensors. After going through several tests, a tool performance has been obtained with the expected characteristics, including the accuracy of sensor readings, the accuracy of LCD control, and the automation of relationships between systems. Furthermore, through the simulation form that has been achieved, it is hoped that this tool can be applied to a more real system with various adjustments and performance improvements.